MORAL VALUES IN MAYA ANGELOU SELECTED POEMS - Shafira Ramadhani Lubis; Ayu Melati Ningsih; Risnawaty Risnawaty; Dewi Nurmala (IKIP Siliwangi, 2024)
The objectives of the study were 1) to describe the form of moral values found in selected poems by Maya Angelou, and 2) to describe how the disclosure of moral values in selected poems by Maya Angelou. In this case, the research used a descriptive qualitative method to classify and analyze the data. This collection of poems is interesting to research because it contains many moral values and very inspiring messages about life, humanity and justice in the poem. The approach used in this research is a pragmatic approach. Based on the results of the analysis, the researcher found three most dominant moral values : Moral Courage, Be Yourself, and Honesty. After finding the moral values in each stanza of the poem, the poem was analyzed to obtain the meaning contained in each stanza.